# Plzzzzzzzzzzzzz hellllllllllllllllllllllllllpppppppppppppppppp

## Answers

Answer 1
Answer:

Answer:

1.02 units3

Step-by-step explanation:

## 18/15 =1.02

Answer 2
Answer: Answer is 1.02 ......

## Related Questions

Rewrite with positive exponents a^-3 b^-5

### Answers

Answer:

1/a^3 and 1/b^5

Write the quadratic equation whose roots are 4
and
−1
, and whose leading coefficient is
2

### Answers

2(x-4)(x+1)
Fundamental Theorem of Algebra essentially states that all polynomials can be reduced down to the product of their roots.

Lysera enjoys exploring her land on horseback with its lush green valleys and ancient forests. She can cover a great deal of ground on her horse, Princess Grey Dawn, traveling at 9 km/h. Unfortunately Lysera has allergies. How far would Lysera and Princess Gray Dawn have moved while Lysera’s eyes were shut for 0.50 s during a hard sneeze? (answer in kilometers)

### Answers

Answer:

0.00125 km.

Step-by-step explanation:

Given,

• Speed of the horse on which princess travelling, v = 9km/h
• Time taken by Lysera to sneeze = 0.5 s

As we know

1 hour = 3600 seconds

So, time taken by Lysera to sneeze can be given by,

According to definition of speed,

=>distance = speed x time

= 0.00125 km

Hence, Princess Gray down will moved by 0.00125 km.

The third and the sixth term of a geometric progression are 24 and 64/9 respectively. Finda) the first term and common ratio
b) the sum of the first five terms​

### Answers

Answer:

Ai. Common ratio = 2/3

Aii. First term = 54

B. Sum of the first five terms = 422/3

Step-by-step explanation:

From the question given above, the following data were obtained:

3rd term (T3) = 24

6Th term (T6) = 64/9

First term (a) =?

Common ratio (r) =?

Sum of the first five terms​ (S5) =?

Ai. Determination of the common ratio (r).

T3 = ar²

T3 = 24

24 = ar²....... (1)

T6 = ar⁵

T6 = 64/9

64/9 = ar⁵......... (2)

The equation are:

24 = ar²....... (1)

64/9 = ar⁵......... (2)

Divide equation 2 by equation 1.

64/9 ÷ 24 = ar⁵ / ar²

64/9 × 1/24 = r³

8/27 = r³

Take the cube root of both side

r = 3√(8/27)

r = 2/3

Thus, the common ratio is 2/3

Aii. Determination of the first term (a).

T3 = ar²

3rd term (T3) = 24

Common ratio (r) = 2/3

First term (a) =?

24 = a(2/3)²

24 = 4a/9

Cross multiply

24 × 9 = 4a

216 = 4a

Divide both side by 4

a = 216/4

a = 54

Thus, the first term (a) is 54

B. Determination of the sum of the first five terms.

Common ratio (r) = 2/3

First term (a) = 54

Number of term (n) = 5

Sum of first five terms (S5) =?

Sn = a[1 –rⁿ] / 1 – r

S5 = 54[1 – (⅔)⁵] / 1 – ⅔

S5 = 54 [1 – 32/243] / ⅓

S5 = 54 (211/243) × 3

S5 = 54 × 211/81

S5 = 6 × 211/9

S5 = 2 × 211/3

S5 = 422/3

Thus, the sum of the first five terms is 422/3

A certain firm has plants a, b, and c producing respectively 35\%, 15\%, and 50\% of the total output. The probabilities of a nondefective product are, respectively, 0.75, 0.95, and 0.85. A customer receives a defective product. What is the probability that it came from plant c?

### Answers

The proportion of production that is defective and from plant A is

... 0.35·0.25 = 0.0875

The proportion of production that is defective and from plant B is

... 0.15·0.05 = 0.0075

The proportion of production that is defective and from plant C is

... 0.50·0.15 = 0.075

Thus, the proportion of defective product that is from plant C is

... 0.075/(0.0875 +0.0075 +0.075) = 75/170 = 15/34 ≈ 44.12%

_____

P(C | defective) = P(C&defective)/P(defective)

### Final answer:

The question required the use of Bayes' theorem to determine the probability of a defective product coming from plant c. Given the probabilities of defectiveness for each plant, the calculation indicated that there is approximately a 54.55% chance that a defective product came from plant c.

### Explanation:

The problem described can be solved using Bayes' theorem, which is a principle in Probability that is used when we need to revise/or update the probabilities of events given new data. Since a defective product is received, and we need to determine the probability of it coming from plant c, we apply Bayes' theorem for the probability of events a, b, and c (representative of the products from the respective plants).

The Bayesian formula we will use, given the probabilities of a, b and c respectively and the probability of receiving a nondefective product from these plants, is: P(c|defective) = [P(defective|c) * P(c)] / [P(defective|a) * P(a) + P(defective|b) * P(b) + P(defective|c) * P(c)].

First, calculate the probability of a defective product from each plant (1 minus the probability of a nondefective product): these are 0.25 for plant a, 0.05 for plant b, and 0.15 for plant c.

Then substitute the values: P(c|defective) = [0.15 * 0.50] / [(0.25 * 0.35) + (0.05 * 0.15) + (0.15 * 0.5)] = 0.075 / 0.1375 = 0.5454545.

So, given a defective product, there is approximately a 54.55% chance that it was produced by plant c.

### Learn more about Bayes' theorem here:

brainly.com/question/34293532

#SPJ11

Find the equation of the line parallel to x=1 that contains the point (-2,-1)

### Answers

answer : x= -2

bc the graph of x=1 is just a straight vertical line across the x-axis, so any lines parallel have to go vertically across the x-axis as well. The graph of line that goes through the point (-2,-1) is x=-2